Connecting local support: A qualitative study exploring the role of voluntary organisations in long-term condition management. (June 2015) - Morris, Rebecca; Kirk, Susan; Kennedy, Anne; Vassilev, Ivaylo; Mathieson, Amy; Jeffries, Mark; Blickem, Christian; Brooks, Helen; Sanders, Caroline; Rogers, Anne
Objectives: To examine the role of community groups to support people living with long-term conditions and the organisational factors that influence this role. Methods: Thirty-three semi-structured interviews were conducted with voluntary group organisers purposefully sampled in Greater Manchester from a local database of community groups. Interviews explored the organisations role in supporting people living with a long-term condition, their social networks and the origins of the groups. Results: Respondents' construed their role in supporting individual capacity for management either explicitly (e.g. providing exercise) or implicitly (e.g. emotional support). This role was influenced by a combination of group ideology, funding and social networks. Analysis highlights the role of the non-clinical setting, the social support provided within the group, as well as organisational processes that influenced their capacity to support people living with long-term conditions. Conclusion: By examining the organisation of voluntary groups, this study highlights the way in which they may support or constrain access to an extended range of support for people with long-term conditions. This paper has implications for commissioning of services by the health service from the third sector because of the differing ideological perspectives and limited operational capacity.